Beyond the energy crisis : opportunity and challenge - International Conference on Energy Use Management (3rd : 1981 : Berlin, Germany); Fazzolare, Rocco; Smith, Craig B. (Oxford : Pergamon Preess, 1981)
Includes bibliographies.